La guerra destruye, la guerra construye. Ensayo sobre el desarrollo del nacionalismo en Sudamérica - Thomas Lyle Whigham (Nuevo mundo - Mundos Nuevos, 2006)
While Brazil and Argentina forged artificial nationalisms that reflected nineteenth-century ideologies of European origin, the Republic of Paraguay developed a conservative nationalism based on narrow traditions of patrimonialism, community solidarity, and a unique linguistic environment defined by the use of the Guaraní language. This form of nationalism, which the Paraguayan state did not initially seek to promote, eventually provided the backdrop for the country’s stubborn resistance to the Allied armies during the course of the Triple Alliance War of 1864-1870.